Model for Developing the Performance of Police Stations under of Provincial Police Region 4: Model for Developing the Performance of Police Stations under of Provincial Police Region 4 - Ratchakaew, Nattawit; Phosing, Pakdee; Kenaphoom, Sanya (RATANABUTH JOURNAL, 2024)
The police are the unit responsible for the safety of people’s lives and property, which must drive the work to achieve the results for the people and the goals of the government and the Royal Thai Police. The research phase 1 aimed to 1) study the level of performance results of police stations and 2) analyze the causal factors of the structural equation model for the development of performance results of police stations. The sample group consisted of 380 police officers. The research instrument was a 5-level rating scale questionnaire. The data were analyzed using statistics, frequency, percentage, mean, standard deviation, structural equation model (SEM) analysis, and confirmatory factor analysis (CFA). Phase 2 research to create and confirm the model for developing the performance of police stations consisted of 1) drafting the model from the research results in phase 1, from the critique by 9 experts through focus group discussions, using the results of the group discussions to improve, and confirming the model through a connoisseurship seminar to confirm the appropriateness of the model. The target population was 20 police administration experts through purposive sampling. Data analysis used content analysis, mode, median, and interquartile range. The research results found that: 1. The overall performance of police stations under the jurisdiction of the Provincial Police Region 4 was at a high level. When separated into each aspect, it was found that all aspects were at a high level. 2. The causal factors of the structural equation model for the development of the performance of police stations under the Provincial Police Region 4 are consistent with the empirical data. Considering the chi-square value, it is not statistically significant (x2/df = 1.596). The CFI value, the comparative fit index, is equal to .974. The Tucker-Lewis Index is equal to .949. When considering the parameter estimation error (RMSEA) of 0.042 and the root mean square of the standard error (SRMR) of 0.031, it was found that all causal factors can directly and indirectly influence the performance of police stations under the Provincial Police Region 4. 3. The model of the development of the performance of police stations under the jurisdiction of the Provincial Police Region 4 by experts (Connoisseurship) found that the model was very consistent ( =Median =4.80, IR =0.24, Mod =4.84, Mo-Mdn =0.04), consisting of relationship development, transformational leadership development, workforce development, and development of police policy implementation as community servants. The model of the development of the performance of police stations under the jurisdiction of the Provincial Police Region 4 is called the “PoLICE MODEL”.